Попытка не пытка: [повесть] / Марина Серова - Серова Марина Сергеевна (Русский бестселлер, 2001)
Экземпляры: Ф. 2 (20191227) / Инвентарный номер: 47500 / Цена: 20.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: С 32 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44